PENGARUH PENYULUHAN KESEHATAN GIGI TERHADAP KETERAMPILAN MENYIKAT GIGI PADA DISABLED CHILDREN DI SLB NEGERI TABANAN - I Gede Surya Kencana; I Made Budi Artawa; Nyoman Gejir (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2022)
Dental health is one of the most important things for children's growth, but in Indonesia there are not many parents who care about their children's dental health, especially children with special needs (disabled children). Children with special needs have a higher risk of dental and oral health problems, this is because they have mental and physical deficiencies and limitations to perform optimal self-cleaning of their teeth. The purpose of this study was to determine the effectiveness of dental health education in improving tooth brushing skills for children with special needs at SLB Negeri Tabanan. This research is a pre - experimental research with one group pre and post test design . The number of respondents in this study were 95 people consisting of 47 men (58.75%) and 33 women (41.25%). brushing skills in Disabled Children before intervention with the category of needing guidance as many as 53 people (55.79%) and tooth brushing skills in Disabled Children after intervention with the category needing guidance as many as 39 people (42.05%) none of the children had the skills brushing teeth with a very good category before and after the intervention. Conclusion By using a one sample test, a sig value of 0.000 was obtained. This value is smaller than 0.005 which means that there is a significant effect of dental health education on brushing skills in disabled children at SLB Negeri Tabanan